EFFECT OF PHYSICAL CONDITIONING ON STUDENT BASIC SKILLS GYMNASTICS - Endang Rini Sukamti; Ratna Budiarti; Risti Nurfadhila (Jurnal Cakrawala Pendidikan, 2020)
Physical conditioning was considered as a strong foundation for developing techniques from different fields. The aims of this study was to determine the impact of physical conditioning in parenting students or athletes gymnastic basic skills. The study was a surveyed research. The study sampling was 82 students aged between 18-19 years from Sport sciences, exactly coaching sciences. Data collection methods used checks and measurements of bio motor and gymnastic fundamental skills. Data analysis using correlation and linear regression to predict the future competence. The results showed that: there was significant correlation between the physical conditioning items and gymnastics basics skills, but there is also strong significant linear regression (p: .032.05)  from physical conditioning with basic skill of Gymnastics. The standing balance (r = .728) and broad jump (r = .751) were found more influenced for gymnastic basic skills. There was a great significant different between the pre-test and posttest gymnastic basic skills means with p value .001. The high standard deviation between the items showed the different adaptation of the subjects according to the physical conditioning. In conclusion physical conditioning was found as parenting for developing the gymnastic basic skills.